Research on the Low-Carbon Development Path and Policy Options of China’s Transportation Under the Background of Dual Carbon Goals - Wang, Xuecheng; Zhou, Yalin; Bi, Qinghua; Cao, Zilong; Wang, Baochun (Frontiers in Environmental Science, 2022)
Chinese government has proposed ambitious targets to combat climate change. As carbon emissions of China’s transportation have been rapidly increasing in past decades, massive efforts for carbon reduction need to be taken by transportation sector. Research on practical action paths for transportation sector’s low-carbon development are critical to achieving the Paris Agreement goals and China’s “Dual-Carbon” Target. Based on the transportation’s historical carbon emissions and the new possible trends in the future, this paper uses a forecast model to predict transportation’s carbon emission. Then we adopt a scenario analysis to analyze the total transportation demand in the transportation sector from 2021 to 2060. We quantitatively simulated the emission reduction effects of different policy measures under different scenarios, such as optimization of transportation structure, application of energy-saving and emission-reduction technologies, and new energy vehicles. The results provide paths and measures for the low-carbon development of transportation, and provides policy suggestion for the scientific formulation of the low-carbon development.